Keynesian fiscal policy and economic recession: the case of the outbreak of the COVID-19 virus - Khamjinda , Dussadee; Chasuwan, Duangnet (Journal of Modern Learning Development, 2023)
This article aims to present fiscal policy and economic recession problems: the outbreak of the COVID-19 virus. Fiscal policy is one activity of intervention in the public economy. There are many ways to solve the economic problems of the government sector. But there is one method that is suitable for the economic downturn. unemployment Due to the production of goods decreased causing people’s purchasing power to decrease. The outbreak of the COVID-19 epidemic has resulted in the closure of private business institutions, leading to unemployment of many people. The government’s use of Keynesian fiscal policy is therefore essential to the macroeconomic system, such as reducing taxes, increasing public employment. Control the price of food and energy products. and deficit expenditure budgeting As a result, the amount of money is circulating in the economy or appears to increase, etc.